PENGARUH BIAYA PEMELIHARAAN AKTIVA TETAP TERHADAP LABA OPERASIONAL PT. TRI TUNGGAL MAKMUR PAMEKASAN - Devi Lestari Pramita Putri; Abdul Jamali (Universitas Methodist Indonesia, 2019)
Cost is one of the important elements in a company. With the right cost management, maximum profit will be created. One of the costs in question is the cost of maintenance of fixed assets. This needs to be done by the company to increase its operating profit because if the company carries out maintenance of its fixed assets appropriately, it will expedite the company's operating processes. Every year, PT. Tri Tunggal Makmur Pamekasan continues to maintain its fixed assets so researchers are interested to see how the costs of maintaining fixed assets affect operating income in the company. Data analysis techniques used in this study are multiple regression analysis and correlation analysis with 3 predictors, coefficient of determination, and F-test using Microsoft Excel. Based on the results of data analysis, the multiple regression equation is obtained, namely, Y = 16.132,824 + 2,097089 X1 + 2.096838 X2 + 0.17042 X3 and has a close relationship (correlation) of 0.91 with a coefficient of determination showing 82, 81% and the Ha hypothesis test that is the cost of maintaining machinery, vehicles, and buildings have a positive effect on operating profit with the resulting F-count of 8.02 and F-table of 5.41 for a significance level of 5%, then Ha is accepted.